Experiences of Burnout among Drug Counselors in A Large Opioid Treatment Program: A Qualitative Investigation. Issue 2 (April 2018) - Beitel, Mark; Oberleitner, Lindsay; Muthulingam, Dharushana; Oberleitner, David; Madden, Lynn M.; Marcus, Ruthanne; Eller, Anthony; Bono, Madeline H.; Barry, Declan T.
Background: Little is known about possible experiences of burnout among drug counselors in opioid treatment programs that are scaling up capacity to address the current opioid treatment gap. Methods: Participants in this quality improvement study were 31 drug counselors employed by large opioid treatment programs whose treatment capacities were expanding. Experiences of burnout and approaches for managing and/or preventing burnout were examined using individual semi-structured interviews, which were audiotaped, transcribed, and systematically coded by a multidisciplinary team using grounded theory. Results: Rates of reported burnout (in response to an open-ended question) were lower than expected, with approximately 26% of participants reporting burnout. Counselor descriptions of burnout included cognitive, affective, behavioral, and physiological symptoms; and job-related demands were identified as a frequent cause. Participants described both self-initiated (e.g., engaging in pleasurable activities, exercising, taking breaks during workday) and system-supported strategies for managing or preventing burnout (e.g., availing of supervision and paid time off). Counselors provided recommendations for system-level changes to attenuate counselor risk of burnout (e.g., increased staff-wide encounters, improved communication, accessible paid time off, and increased clinical supervision). Conclusions: Findings suggest that drug counselor burnout is not inevitable, even in opioid treatment program settings whose treatment capacities are expanding. Organizations might benefit from routinely assessing counselor feedback about burnout and implementing feasible recommendations to attenuate burnout and promote work engagement.